(untitled) (Eurasian Journal of Ecology, 2020)
The purpose of this study is screening and isolation of thermophilic microorganisms from a geothermal hot spring in Zharkent, Almaty region, Kazakhstan. The phylogenetic diversity and screening of the prokaryotic community thriving in Zharkent geothermal hot spring has been studied by microbiological methods. The study confirmed that isolates from Zharkent geothermal hot spring are true thermophiles according to experiments and can be a source of thermostable enzymes; three isolates (AC1W, AC1S, AC4S) out of eight showed good enzymatic characteristics based on the results of their cultivation on selective media. Isolated thermophilic microorganisms, were cultivated under different conditions, such as: temperature (50, 60, 70, 80, and 95оC), selective media (for the amylase, cellulase, and lipase producer), different pH (5, 6, 7, 8, and 10). Morphological features of the isolated bacterial strains were examined by scanning electron microscopy (SEM). Based on the data of biochemical tests and morphological characteristics (endospore formation, aerobic, positive for catalase and oxidase, optimal growth temperature of 75-85 °C and the optimal pH range of growth is 7.5-8), isolated bacteria were presumably listed in the genus Geobacillus. Thus, our research has shown that there is a rich variety of thermophilic microorganisms in Zharkent hot springs, which must be studied to obtain commercially important enzymes. Key words: hyperthermophiles, hydrolase, extremozymes, isolates